Obtaining a Recombinant Nucleoprotein of the Puumala Virus for Serological Diagnostics of Hemorrhagic Fever with Renal Syndrome - A. E. Tishin; S. A. P’yankov; E. Yu. Prudnikova; I. R. Imatdinov (Проблемы особо опасных инфекций, 2025)
Puumala virus (Orthohantavirus puumalaense) is one of the causative agents of hemorrhagic fever with renal syndrome (HFRS), which is widespread in the Russian Federation (RF): more than 6 thousand cases of HFRS infection are registered annually, over the past decade (2013–2023) – more than 77 thousand cases of the disease were reported. Puumala virus causes up to 98 % of HFRS cases. The development of rapid and highly accurate diagnostic methods, including serological test systems, is of great importance in clinical and laboratory studies aimed at controlling viral infections. The aim of the work was to obtain a recombinant viral immunodominant protein, the nucleoprotein (N), of the Puumala virus, and to study its antigenic properties. Materials and methods. Expression constructs were produced using standard molecular-biological methods. The recombinant nucleoprotein of the Puumala virus was purified in two rounds of metal-chelate affinity chromatography. The antigenic properties of the purified recombinant protein were confirmed by Western blotting and enzyme immunoassay using monoclonal antibodies and convalescent blood sera. Results and discussion. Within the frames of this work, prokaryotic producers have been generated for the production and chromatographic purification of the recombinant nucleoprotein N of the Puumala virus. Using Western blotting and enzyme immunoassay, specific antigenic properties of the recombinant chromatographically purified Puumala virus N protein have been confirmed. Two consecutive rounds of metal-chelate affinity chromatography allowed us to obtain a highly purified recombinant viral protein preparation. The results demonstrate the antigenic specificity of the recombinant chromatographically purified Puumala virus proteins. The preparations can be used to develop serological test systems, including for differentiating vaccinated people from those who have recovered.